Paper 19: The Influence of Amniotic Suspension Allografts and Bone Marrow Aspirate Concentrate on Inflammation & Cartilage Matrix Metabolism in Osteoarthritic Chondrocytes. Issue 7 (30th July 2022) - Hannon, Charles; Dandu, Navya; Huddleston, Hailey; McIlwraith, Wayne; Frisbie, David; Hakimiyan, Arnavaz; Chubinskaya, Susan; Cole, Brian; Yanke, Adam
Objectives: While bone marrow aspirate concentrate (BMAC) and amniotic suspension allografts (ASA) have all garnered clinical interest for the treatment of osteoarthritis, basic science evidence supporting their use is lacking. Specifically, there is a paucity of literature on the in vitro effects of BMAC and ASA on inflammation and cartilage matrix metabolism in OA chondrocytes and synoviocytes. The purpose of this study was to evaluate the effect of BMAC and ASA on inflammation and cartilage metabolism in a model that mimics the OA intra-articular environment: a co-culture of OA cartilage explants and synoviocytes. Methods: After institutional IRB approval, 17 patients were enrolled at the time of total knee arthroplasty for donation of cartilage, synovium, and bone marrow aspirate tissue samples. All patients had Kellgren-Lawrence Stage 2 or 3. The aspirate was then be prepared and centrifuged using a standard commercially available BMAC centrifuge system, typically yielding up to 3mL of BMAC. Synoviocyte and cartilage explant co-culture systems were created using 24-well culture plates containing 0.4mm filtered inserts. Four co-culture systems were established per patient to accommodate the 2 biologic treatment groups (BMAC and ASA), one control group at 96 hours, and one baseline control cartilage group. Multiplex ELISA was used to measure concentrations of pro-inflammatory mediators interleukin – 1b (IL-1b), interleukin – 6 (IL-6), and tumor necrosis factor – alpha (TNF–a) at 96 hours. Each sample was measured in duplicate to ensure accuracy. Additionally, both chondrocyte and synoviocyte RNA were assayed for collagen type I a1 ( COL1A1 ), collagen type II a1 ( COL2A1 ), collagen type III a1 ( COL3A1 ), aggrecan ( ACAN ), and cartilage oligomeric matrix protein ( COMP ). All statistical analyses were performed on STATA v16.1. Normality of data was determined by Shapiro-Wilk test, and non-parametric or parametric tests were utilized where appropriate. Results: There were no significant differences in cytokine concentration between the 96-hr control group and the BMAC co-culture for any cytokine, although IL-6 was trending towards significance (Control: 856.3 ± 346.2 vs BMAC: 662.3 ± 346.8, p=.08). There was a significantly lower concentration of IL-1B in the ASA group compared to the control group (ASA: 11.2 ± 13.9 vs Control: 20.2 ± 39.5, p=.04) (Table 1 ). No significant differences in expression were observed for Col1A1, Col2A1, Col3A1, COMP or ACAN in either cartilage or synovium samples across the three groups. Conclusions: The early results from this study suggest that ASA may have anti-inflammatory properties and promote the expression of major extracellular matrix genes in both osteoarthritic chondrocytes and synoviocytes involved in cartilage matrix metabolism. Specifically, ASA was associated with decreased concentrations of IL-1ß. The use of intra-articular therapies as sources of growth factors, anti-inflammatory mediators, and potentially mesenchymal stem cells (MSCs) for OA is rapidly evolving. MSCs have garnered significant interest due to their chondrogenic potential and promise for tissue regeneration. Two commercially available sources of MSCs are bone marrow aspirate concentrate (BMAC) and amniotic membrane. As biologics garner more attention in the clinical setting, their underlying mechanisms and efficacy in in-vitro models become important to elucidate. The results from this study provide basic science support for further clinical trials comparing ASA and BMAC to current standard of care corticosteroid injections for OA. Table 1. Luminex Assay for Cytokine Concentrations in Media